Identification and analysis of influencing factors of green mining construction based on DPSIR model and Fuzzy-DEMATEL approach - Lin, Weixing; Wu, Pan; Zhao, Guoyan (Frontiers in Environmental Science, 2024)
Green mining construction (GMC) is a sustainable mining development model with the potential of realizing synergistic development of resources, environment, society, and economy. At present, the green mining strategy has yielded some successes, but there is still a significant gap between theoretical research and practical promotion, owing to the complexity of the green mining system and the diversity of influencing factors. Therefore, in the context of current pressure to normalize environmental protection, how to promote the construction of green mines while taking into account the premise of economic development has become an important issue. Inspired by the form of Drive-Pressure-State-Impact-Response (DPSIR) model, this paper constructs a DPSIR model of the driving mechanism of green mining construction. Using the fuzzy-DEMATEL method, each critical factor and influencing mechanism of GMC is explored, and the network relationship of the critical factors is established. The results show that many factors affect GMC from the perspective of the ecological environment, and 11 critical factors are obtained in varying degrees. Among them, green technology and supervision and long-term mechanism are the most important and influencing factors. Based on the transmission mechanism among these factors, improvement suggestions, and specific strategies are put forward. This research effectively identifies and analyzes the critical factors of GMC from the perspective of driving and response mechanisms, which is helpful to support the construction of ecological civilization and the sustainable development of mining industry.